The Influence Of Occupational Safety And Health (K3), Organizational Culture, And Leadership Style On Employee Performance Mediated By Job Satisfaction At PT Angkasa Pura Aviasi - Rizky Ramadhansyah Harahap; Yohny Anwar; Sri Rahayu (Yayasan Multidimensi Kreatif, 2025)
This study aims to analyze the influence of occupational safety and health (K3), organizational culture, and leadership style on employee performance, with job satisfaction as a mediating variable. The study was conducted on 85 employees of PT Angkasa Pura Aviasi using a quantitative method with SEM-PLS analysis. The results of the study show that (1) Occupational Safety and Health (K3) has a positive and significant effect on employee performance. (2) Organizational culture does not have a significant effect on employee performance. (3) Leadership style has a positive and significant effect on employee performance. (4) Occupational Safety and Health (K3) has a positive and significant effect on job satisfaction. (5) Organizational culture does not have a significant effect on job satisfaction. (6) Leadership style has a positive and significant effect on job satisfaction. (7) Job satisfaction has a positive and significant effect on employee performance. (8) Occupational Safety and Health (K3) does not have a significant effect on employee performance through job satisfaction. (9) Organizational culture does not have a significant effect on employee performance through job satisfaction. (10) Leadership style has a positive and significant effect on employee performance through job satisfaction. These results show that improved work safety and effective leadership styles play an important role in improving employee satisfaction and performance. In contrast, organizational culture does not show significant influence. The implication of this study is the need for management to strengthen the implementation of OSH and transactional leadership to support employee productivity.